Venous thromboembolism prophylaxis after hip preservation surgery: a review and presentation of institutional experience. Issue 3 (1st October 2018) - Aali Rezaie, Arash; Azboy, Ibrahim; Parvizi, Javad
ABSTRACT: Venous thromboembolism (VTE) is a serious complication after major orthopedic procedures. The best options for prevention of the VTE are still debated. The most popular evidence-based guidelines for prevention and treatment of VTE in orthopedic surgery addressed the total hip or knee arthroplasty and hip fractures as the major orthopedic surgeries. Majority of studies have evaluated the different modalities of the VTE prophylaxis in patients undergiong hip or knee arthroplasty. Hip preservation surgeries (HPS) including mini-open femoroacetabular osteoplasty, surgical dislocation of the hip, arthroscopic procedures, and periacetabular osteotomy (PAO) are gained popularity in recent two decades. The majority of these patients are young, healthy and active and may not be considered at high risk for VTE. The frequency of VTE in patients undergoing PAO seems to be low between 0 and 5%. There is a paucity of data regarding rates of VTE in young healthy patients undergoing HPS as well as the optimal prevention methods for VTE. Hence current VTE prevention guidelines do not cover HPS adequately. We aimed to review the available literature regarding VTE events and VTE prophylaxis options after HPS. We discussed the available and potential options for prophylaxis of VTE events in these procedures along with our experience in a large cohort of hip preservation surgery.